Radiation adaptive response: the biophysical phenomenon and its theoretical description - Fornalski, Krzysztof W; Adamowski, Łukasz; Bugała, Ernest; Jarmakiewicz, Rafał; Krasowska, Julianna; Piotrowski, Łukasz (Radiation protection dosimetry, 2024)
The radiation adaptive response (or radioadaptation) effect is a biophysical and radiobiological phenomenon responsible for, e.g. the enhancement of repair processes, cell cycle and apoptosis regulation or enhancement of antioxidant production in cells/organisms irradiated by low doses and low dose-rates of ionising radiation. This phenomenon, however, is not always present, which creates many problems both for experimenters and theoreticians. Here we propose a comprehensive and complete theoretical model of radioadaptation grounded in mathematical concept of dose- and time-related probability function of the adaptive response appearance. This can be used in the context of two special cases of the adaptive response: the Raper-Yonezawa (priming dose) effect or constant low-dose-rate irradiation (e.g. for high natural background). This complete theoretical approach is supported by Monte Carlo simulations and real-experimental data used for model calibration and validation.